2001
DOI: 10.1115/1.1409259
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects Between Surface Radiation and Turbulent Natural Convection in Square and Rectangular Enclosures

Abstract: The interaction effects of surface radiation with turbulent natural convection of a transparent medium in rectangular enclosures have been numerically analyzed, covering a wide range of Rayleigh number from 109 to 1012 and aspect ratio from 1 to 200. The vertical walls of the enclosure are isothermal and maintained at different temperatures. The adiabatic top and bottom walls of the enclosure have been modelled for the limiting cases of negligible or perfect conduction along their lengths. The interaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 18 publications
3
41
2
1
Order By: Relevance
“…The mean Nusselt number Nu m calculated using the turbulent model was compared with those reported in Refs. [25][26][27][28][29]. The comparison revealed better agreement of the model results with the experimental data than the others as shown in Table 2.…”
Section: Numerical Algorithmmentioning
confidence: 64%
See 3 more Smart Citations
“…The mean Nusselt number Nu m calculated using the turbulent model was compared with those reported in Refs. [25][26][27][28][29]. The comparison revealed better agreement of the model results with the experimental data than the others as shown in Table 2.…”
Section: Numerical Algorithmmentioning
confidence: 64%
“…The computational results are compared to the experimental data in Table 2. The table also presents numerical results by Dixit and Babu [26], Le Que're [27], Velusamy et al [28], Henkes [29] for the same benchmark case. The mean Nusselt number Nu m calculated using the turbulent model was compared with those reported in Refs.…”
Section: Numerical Algorithmmentioning
confidence: 92%
See 2 more Smart Citations
“…Several authors [31][32][33][34] showed by experimental and numerical approaches that these two heat transfer modes occur simultaneously. Ramesh and Venkateshan 32 showed experimentally that for a square enclosure (vertical walls maintained at 35 and 65°C, adiabatic horizontal walls, Ra = 5 × 10 5 ), the heat transfer by convection and radiation between high emissive vertical walls (ε = 0.85) is twice of that of polished ones (ε = 0.05).…”
Section: Heat Transfer and Airflow In Empty Closed Cavitymentioning
confidence: 99%